Metode Deteriorasi Terkontrol untuk Pendugaan Daya Simpan Benih Kedelai - ., Nizaruddin; Suwarno, Faiza C.; Widajati, Eny; Qadir, Abdul (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2014)
ABSTRACTPhysiological quality of soybean seeds was easily deteriorated during storage. The objectives of the research were to determine controlled deterioration test which could be used to evaluate soybean seed viability and to find the appropriate controlled deterioration test for estimating storability of soybean seed. The research was conducted at the quality control laboratory PT. BISI International, Tbk., Kediri since October 2012 until February 2013. The completely randomized design with four replications was used in the experiment by moisture content and deterioration periods as treatment. The results showed that the controlled deterioration periods to evaluate two varieties of soybean seed were same for 16 hours at 17.5% moisture content for Wilis and 15% moisture content for Detam-1. The result also showed that there were significant correlations between controlled deterioration values with actual values from 16 weeks storage periods, indicating controlled deterioration test periods could estimate storage periods. Verification of seed vigor relation to storability model showed there were no significant differences between germination and speed of germination between controlled deterioration and actual values. Simulation of soybean seed storability model with germination percentage after controlled deterioration as input variables could predict the storage periods.Keywords: Glycine max, rapid ageing, seed modelling, seed vigour, vigour index